Evaluacion de niveles de hormonas fsh, lh, estrógenos y progesterona en llamas hembras (Lama glama) en edad reproductiva - Almachi Almache, Rosa Marina (2016)
The female lamas does not have estrous cycles as in other domestic species, this presents long periods of receptivity and short periods of no receptivity. Therefore, the objective of the present investigation is to determine serum hormone concentrations of FSH, LH, estrogen and progesterone burning age 1 to 4 years in relation to the altitude. Group 1 = 4 animals (altitude 2685 m corresponding to the Experimental and Production Center Salache) and group 2 = 4 animals (altitude 3180 meters above sea level belongs: on the Run 8 females of reproductive age who were divided into two groups were used Ticatilin the sector). The femoral artery of each animal blood samples, which were processed in the laboratory by Chemiluminescence analysis, was obtained....